2000
DOI: 10.1093/cercor/10.10.927
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dendritic Spine Morphology by the Rho Family of Small GTPases: Antagonistic Roles of Rac and Rho

Abstract: Dendritic spines mediate most excitatory transmission in the mammalian CNS and have been traditionally considered stable structures. Following the suggestion that spines may 'twitch', it has been recently shown that spines are capable of rapid morphological rearrangements. Because of the role of the small GTPases from the Rho family in controlling neuronal morphogenesis, we investigated the effects of several members of this biochemical signaling pathway in the maintenance of the morphology of extant dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
345
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(376 citation statements)
references
References 38 publications
26
345
3
2
Order By: Relevance
“…Previously, we showed that unlike Rac1, which is expressed at high levels from the early stage and persists throughout development, RhoA expression levels are low at the early developmental stage but gradually increase, and after DIV 20, its expression levels are comparable with those of Rac1 (30). Besides, it is well known that RhoA and Rac1 exert antagonistic effects in spine development: RhoA plays a negative role, whereas Rac1 plays a positive role (31). Because the previous studies showed that PLD or PA is directly recruited to the plasma membrane and activates Rac1 or RhoA (32-34), we hypothesized that the balance between ARF6-T157A-induced Rac1 and RhoA activation via the PLD pathway, bypassing the PAK/RhoGDI pathway, plays a key role in the spine-reducing effect of ARF6-T157A in mature neurons (see also Fig.…”
Section: Arf6 Distinctly Modulates Dendritic Spine Formation At Eachmentioning
confidence: 94%
“…Previously, we showed that unlike Rac1, which is expressed at high levels from the early stage and persists throughout development, RhoA expression levels are low at the early developmental stage but gradually increase, and after DIV 20, its expression levels are comparable with those of Rac1 (30). Besides, it is well known that RhoA and Rac1 exert antagonistic effects in spine development: RhoA plays a negative role, whereas Rac1 plays a positive role (31). Because the previous studies showed that PLD or PA is directly recruited to the plasma membrane and activates Rac1 or RhoA (32-34), we hypothesized that the balance between ARF6-T157A-induced Rac1 and RhoA activation via the PLD pathway, bypassing the PAK/RhoGDI pathway, plays a key role in the spine-reducing effect of ARF6-T157A in mature neurons (see also Fig.…”
Section: Arf6 Distinctly Modulates Dendritic Spine Formation At Eachmentioning
confidence: 94%
“…Of particular interest is the Rho-family of guanosine triphosphatases (GTPases), a subfamily of the Ras superfamily of GTPases, which stimulate a wide array of cellular processes, including morphogenesis, cell migration, mitosis, and adhesion [21][22][23]. The Rho subfamily is further divided into 7 subfamilies (Rho, Rac, Cdc42, Rnd, RhoD, RhoBTB, and RhoH), of which the most extensively studied members are RhoA, Rac1, and Cdc42 for their role in regulating the actin cytoskeleton, the main structural component of dendritic spines, and thus in controlling spine dynamics [24][25][26][27]. Because of their important roles in various cellular processes, their activities are tightly spatiotemporally regulated to ensure homeostasis.…”
Section: Rho-guanosine Triphosphatases At the Center Of Ad Pathologymentioning
confidence: 99%
“…This is not surprising, because it has been shown previously that GST N19RhoA is a poor reagent to study Rho inactivation. N19RhoA is mostly insoluble when purified from bacteria (Self and Hall, 1995) and is a relatively weak inhibitor of Rho action (Tashiro et al, 2000). Its ineffectiveness may be a result of poor protein stability (Self and Hall, 1995).…”
Section: Rho Inhibition Enhances Drg Outgrowth On Inhibitory Substratesmentioning
confidence: 99%